جبران خليل جبران متصوفا - بن عمر, سهيلة (University of El-oued, 2019)
الأدب هو تعبير الإنسان عن نفسه ، فالأدب بهذا المعنى رسولي ، يحاول من خلاله الأديب تقديم رؤى وتصورات حول الحياة وتحديد موقف الإنسان من ذاته ، ومن هذه الحياة المادية المطلقة التي يعيش فيها ، ويغيب عنها البعد الروحاني والعاطفي ... هذه الإشكالية أو الأزمة التي يعيشها الإنسان المعاصر ، حاول الأدب تناولها والبحث عن حلول لها من خلال أجناسه المختلفة ( الشعر ، الرواية ، القصة ، المسرح ... ) ، وإن عمَّ هذا التناول فإنه يبقى لجماعة الرابطة القلمية خصوصية التناول والطرح لهذه الأزمة التي أخذت منحى المشروع الفكري والأدبي تنجلي من مختلف أعمالهم الفنية التي تميزت برؤياهم للإنسان والحياة والكون . هذا التوجه أكثر ما نلاحظه في كتابات جبران خليل جبران وميخائيل نعيمة ، التي تميزت ببعدها الفكري والثقافي وطابعها الديني ومنهجها الذي ضمَّ العديد من القضايا ( قضية وحدة الوجود ، قضية الحياة ، قضية التصوف ...) ، هذا البعد الروحي في كتاباتهم دفعنا إلى تناولها بالدراسة والتحليل لالتماس أبعادها الصوفية وملامحها الروحانية والبحث عن علاقة الأدب بمجال التصوف والصوفية ، وما الرسالة التي حاولا تجسيدها جبران في الأدب المهجري ؟ وما علاقة فعل الهجرة والاغتراب بعالم الصوفية وتجربة التصوف ؟ وكيف نسج أدب الرابطة القلمية هذه المعالم الصوفية لغويا وفنياً وجماليا في أدبهم ؟ . ما الرسالة التي قدمها جبران للقارئ في التضمين الروحي والصوفي لأدبهم وانفتاحه على التصوف في مصادره المشرقية حتى الغربية ؟ Literature is man’s expression of himself. Literature in this sense is apostolic, through which the writer tries to present visions and perceptions about Life and the determination of man’s position on himself, and from this absolute material life in which he lives, absent from it the spiritual and emotional dimension ... this The problematic or crisis that contemporary man lives, which literature tried to address and search for solutions to it through his different genders (poetry The novel, the story, the theater ...), and if this approach is generalized, then the Pen League will have a specificity of dealing with and addressing this crisis that The approach of the intellectual and literary project was evident from their various artistic works that were characterized by their visions of man, life and the universe. This trend is most noticeable in the writings of Gibran Khalil Gibran and Mikhail Naima, which were distinguished by their intellectual and cultural dimension and character The religious approach and its approach which included many issues (the issue of pantheism, the issue of life, the issue of mysticism ...), this dimension The spiritual in their writings prompted us to study and analyze it in order to seek its mystical dimensions and its spiritual features, and to search for the relationship of literature In the field of Sufism and Sufism, and what is the message that Gibran tried to embody in migratory literature? What is the relationship of the act of immigration and alienation with a world? Sufism and the experience of mysticism? How did the literature of the Pen League weave these mystical features linguistically, artistically and aesthetically into their literature? . . What is the message that Gibran presented to the reader regarding the spiritual and mystical embedding of their literature and his openness to Sufism in its Eastern even Western sources?
مقال. Ex Professo. مج4. ع.1. جامعة الوادي
Keywords: Diacritical concordance – Structural mark – Parsing mark – Mark deletion– Tracking; وحدة الوجود ؛ التجلي ؛ الصوفية ؛ املحبة ؛ النور؛ الطبيعة ؛ التقمص